Development of Small Countries in the Business Environment of the European Union - Rajko TOMAŠ; Mirjana RADOVIC-MARKOVIC (Transylvanian Review of Administrative Sciences, 2018)
In this study, we examined whether small countries, when joining the European Union and transferring a part of their sovereignty to the EU institutions, become economically stronger or weaker. We have conducted our assessment based on the index of relative concentration of power (IRC), which was developed for the purpose of this analysis, modifying the Herfi ndahl- Hirschman Index. Our analysis has shown that in the analyzed period between 2000 and 2015, the relative economic power of small member states of the EU grew stronger, while, at the same time, the relative economic power of large countries weakened. We started from the assumption that small countries, prior to their entry into the European Union, have lower competitiveness due to the relatively higher fi xed costs in the public and private sector. Large single market of the European Union produces relatively stronger effect of economies of scale for small countries compared to large countries, which is why their relative economic power grows faster than the relative power of large countries. Keywords: small countries